2012
DOI: 10.1016/j.jtcvs.2011.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Single-patch, 2-patch, and caval division techniques for repair of partial anomalous pulmonary venous connections: Does it matter?

Abstract: Surgical treatment of partial anomalous pulmonary venous connections is associated with excellent outcomes. The overall incidence of late superior vena caval or pulmonary vein stenosis is low. Although not significant, the 2-patch technique might be associated with a greater incidence of sinus node dysfunction and late pulmonary venous stenosis. The late development of superior vena caval obstruction is a concern with all techniques, necessitating close follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 15 publications
3
47
0
2
Order By: Relevance
“…The results of the Warden procedure first reported in 1983 showed a decreased incidence of rhythm disturbances by avoiding incisions through the SVC‐RA junction . When previous studies compared single‐ and double‐patch procedures, most of the studies concluded that the double‐patch procedures increased the risk of sinus node dysfunction . Although the Warden procedure offers the best option to avoid postoperative rhythm disturbances by avoiding cavo‐atrial junction incisions, it may still lead to arrhythmias from the suture of the intracardiac patch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the Warden procedure first reported in 1983 showed a decreased incidence of rhythm disturbances by avoiding incisions through the SVC‐RA junction . When previous studies compared single‐ and double‐patch procedures, most of the studies concluded that the double‐patch procedures increased the risk of sinus node dysfunction . Although the Warden procedure offers the best option to avoid postoperative rhythm disturbances by avoiding cavo‐atrial junction incisions, it may still lead to arrhythmias from the suture of the intracardiac patch.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 When previous studies compared single-and double-patch procedures, most of the studies concluded that the double-patch procedures increased the risk of sinus node dysfunction. 4,13 Although the Warden procedure offers the best option to avoid postoperative rhythm disturbances by avoiding cavo-atrial junction incisions, it may still lead to arrhythmias from the suture of the intracardiac patch. This baffle must be sutured without transmural bits around the opening of the SVC.…”
Section: Discussionmentioning
confidence: 99%
“…4-0.7% of the population at autopsy (2). These anomalies are most frequently identified in children, where they are typically right sided and are associated with ASDs in 80-90% of cases (1,2). In the pediatric population, repair is indicated when pulmonary-to-systemic flow ratio (Qp/Qs) approaches 1.5 (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…PAPVCs are encountered in approximately 0.5% of the pediatric population, where they are commonly associated with atrial septal defects (ASDs) (1). Within this cohort, treatment often requires operative repair (1).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques involving one patch, two patches, or caval division have been used and largely depend on the location of the aberrant pulmonary veins. [1][2][3][4] Low pulmonary veins draining to the right atrium or the cavoatrial junction can generally be repaired with a single patch. Pulmonary veins draining higher in the superior vena cava are typically better served with caval division, pulmonary vein baffling, and reconstruction of the systemic venous pathway by direct anastomosis of the superior vena cava to the right atrial appendage (Warden procedure).…”
mentioning
confidence: 99%